A facile method to fabricate versatile keratin cryogels for tissue engineering applications - Zhao, Zhitong (2024)
Human hair keratin (HHK) has been extensively explored as a biomaterial for soft tissue regeneration due to their excellent bioactivity and biocompatibility. The possibility to fabricate HHK into three-dimensional (3D) hydrogels with physical properties resembling soft tissues has been well demonstrated. However, conventional keratin hydrogels often exhibit a dense architecture that could hinder cell filtration. In the present study, HHK-based cryogels were fabricated using a freeze-thaw method, where oxidized dopamine (ODA) was employed to covalently crosslink thiol/amine rich-keratin molecules at sub-zero temperatures. The obtained HHK-ODA cryogels have micron-sized pores ranging between 100-200 µm and mechanical properties that can be tuned by varying the crosslinking density between ODA and HHK. Through optimization of the weight content of ODA and the number of freeze-thaw cycles, the compressive strengths and stiffnesses of these cryogels achieved 15-fold increments from ~1.5 kPa to ~22 kPa and ~300 Pa to ~5000 Pa, respectively. The HHK-ODA cryogels competently supported human dermal fibroblast spreading and proliferation. Overall, this study exhibited a facile method to fabricate mechanically superior keratin-based cryogels with cell compatible microarchitecture, circumventing the need for complicated chemical modifications and the use of cytotoxic crosslinkers.